No unmet needs without needs! Assessing the role of social capital using data from European social survey 2014. - Quintal, Carlota; Lourenço, Óscar; Ramos, Luís Moura; Antunes, Micaela (Health Policy, 2019)
This paper examines the determinants of unmet healthcare needs in Europe. Special emphasis is put on the impact of social capital. Data come from the European Social Survey, 2014. Our study includes 32,868 respondents in 20 countries. Because unmet needs are observed only in those individuals who are exposed to, and recognise, the need of medical care, sample selection can be an issue. To address it, we analyse the data using the bivariate sample selection model. When there is no need, there is no assessment of access to healthcare. Accordingly, in this situation, our model assumes that unmet need is unobserved. The magnitude and statistical significance of the error correlation support our modelling strategy. A high proportion (18.4%) of individuals in need in Europe reported unmet needs. Informal connections seem to mitigate barriers to access as well as trust in other people and institutions, particularly in health services. Financial strain still is a strong predictor of unmet needs. Other vulnerable groups include informal carers, minorities and individuals feeling discriminated. Unmet needs might also arise due to persistent needs of healthcare as it seems to be the case of individuals with lower health status and chronic conditions. A result that merits further research concerns the positive impact of civic engagement on unmet needs.